SUPLEMEN PAKAN UREA MOLASES BLOK (UMB) BAGI MASYARAKAT PETERNAK - Djunu, Sri Suryaningsih; Saleh, Ellen J; Zainudin, Srisukmawati; Syahruddin, Syahruddin (Universitas Negeri Gorontalo, 2023)
ABSRACT This service aims to increase knowledge and motivate farmer community group participants in Lonuo village, Tilongkabila sub-district, Bone Bolango Regency in utilizing local feed originating from food crop waste as cattle feed in the form of a urea molasses block (UMB) feed supplement. The results of the activity showed that the level of knowledge of the participants about the material for making UMB supplement feed before the training was 07.00% and after counseling and demonstrations their knowledge increased by 93.00%. The existence of this training activity by the community is very helpful because it can open the insights of breeders in utilizing food crop waste which so far has only been wasted and not utilized.Keywords: Urea Molasses Block, Food Crop Waste. ABSTRAK Pengabdian ini bertujuan meningkatkan pengetahuan serta menumbuhkan motivasi peserta kelompok masrakat peternak di desa Lonuo kecamatan Tilongkabila Kabupaten Bone Bolango dalam memanfaatkan pakan lokal yang berasal dari limbah tanaman pangan sebagai pakan ternak sapi dalam bentuk suplemen pakan urea molases blok (UMB). Hasil kegiatan diperoleh bahwa tingkat pengetahuan peserta tentang materi pembuatan pakan suplemen UMB sebelum pelatihan adalah 07,00% dan setelah dilakukan penyuluhan dan demonstrasi pengetahuanya meningkat 93,00%. Adanya kegiatan pelatihan ini oleh masyarakat dirasa sangat membantu karena dapat membuka wawasan peternak dalam memanfaatkan limbah tanaman pangan yang selama ini hanya terbuang dan tidak termanfaatkan. Kata Kunci: Urea Molases Blok, Limbah Tanaman Pangan.